ANALISIS KREDIT BERMASALAH PADA BANK “X” PERIODE 2007-2010 - Marwansyah, Sofyan (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2013)
Banks play an important role in the economy because banks can promote the growth and development especially in the economic field. In carrying out its function as an intermediary institution should optimize the lending bank to its customers. However, loans granted by the bank did not rule out the risk, and therefore an analysis needs to be done so we can figure out how to set up a bank lending. Based on the details of non-performing loans (NPL) in table III.1, III.2, III.3 Where the average - average non-performing loans (NPL) Bank "X" Bank credit risk level "X" in the category of low, level of non-performing loans in the Bank "X" in the year 2007-2010 can be categorized either as it is still below 5%, a decline in NPL Every year the largest occurred in 2008 amounted to 0.90%, while thesmallest occurred in 2009 which is 0.81%, According to the analysis the authors that Bank credit policy in the "X" less selective.